Biochemical characterization of two novel mutations in the human high-affinity choline transporter 1 identified in a patient with congenital myasthenic syndrome. Issue 9 (5th January 2023) - Rizvi, Midhat; Truong, Tina K; Zhou, Janet; Batta, Manav; Moran, Ellen S; Pappas, John; Chu, Mary Lynn; Caluseriu, Oana; Evrony, Gilad D; Leslie, Elaine M; Cordat, Emmanuelle
Abstract: Congenital myasthenic syndrome (CMS) is a heterogeneous condition associated with 34 different genes, including SLC5A7, which encodes the high-affinity choline transporter 1 (CHT1). CHT1 is expressed in presynaptic neurons of the neuromuscular junction where it uses the inward sodium gradient to reuptake choline. Biallelic CHT1 mutations often lead to neonatal lethality, and less commonly to non-lethal motor weakness and developmental delays. Here, we report detailed biochemical characterization of two novel mutations in CHT1, p.I294T and p.D349N, which we identified in an 11-year-old patient with a history of neonatal respiratory distress, and subsequent hypotonia and global developmental delay. Heterologous expression of each CHT1 mutant in human embryonic kidney cells showed two different mechanisms of reduced protein function. The p.I294T CHT1 mutant transporter function was detectable, but its abundance and half-life were significantly reduced. In contrast, the p.D349N CHT1 mutant was abundantly expressed at the cell membrane, but transporter function was absent. The residual function of the p.I294T CHT1 mutant may explain the non-lethal form of CMS in this patient, and the divergent mechanisms of reduced CHT1 function that we identified may guide future functional studies of the CHT1 myasthenic syndrome. Based on these in vitro studies that provided a diagnosis, treatment with cholinesterase inhibitor together with physical and occupational therapy significantly improved the patient's strength and quality of life.